Contrast-induced nephropathy - prevention and treatment - Mateusz Bajak; Julia Słowik; Daniel Zapasek; Michał Szczepański; Maciej Mamczur; Dominik Maciej Feret; Jadwiga Inglot; Julia Inglot; Marcin Kuliga; Damian Sowa; Katarzyna Widawska (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Contrast-induced nephropathy (CIN) is kidney damage that can occur after the administration of contrast agents used in medical imaging procedures like angiography and CT scans. The exact mechanism is not fully understood but is believed to involve direct toxic effects, changes in kidney blood flow, and inflammation. Diagnosis is based on increased serum creatinine levels after contrast exposure. CIN poses challenges due to the rising use of contrast imaging, an aging population, and the increasing prevalence of chronic conditions like diabetes and hypertension. The Aim of this article is to summarize information on how to  prevent contrast-induced nephropathy. Review of medications and pre-procedural screening and monitoring helpful to lower risk of CIN.  State of knowledge: Contrast-induced nephropathy (CIN) is a form of kidney damage that may occur following the administration of contrast agents used in medical imaging procedures. The exact mechanism of contrast-induced nephropathy is not fully understood, but it is believed to involve a combination of factors, including the direct toxic effects of the contrast agent on kidney cells, changes in blood flow to the kidneys, and the body's inflammatory response,  direct effect of oxygen free radicals. The diagnosis of CIN is typically based on an increase in serum creatinine levels within a certain time frame after the administration of the contrast agent. According to European guidelines, the definition of CIN is increased creatinine level in serum by 25% from baseline or  creatinine total level in serum increased by 0.5 mg/dL (44 µmol/L)  48-72h after contrast media administration.   Material and methods. A review of the available literature of PubMed database from 1992 - 2024.